IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL ADMINISTRASI KEPENDUDUKAN - Saiful Deni; Thamrin Husain; Djamila Abbas (JIANA ( Jurnal Ilmu Administrasi Negara ), 2015)
Implementation of Minimum Service Standards Policy Population Administration in the North Maluku Province. This study aims to determine the minimum service standards policy implementation population administration in the Province of North Maluku. The method used is descriptive qualitative. The study population is the entire user population administration services. Techniques of data collection using the questionnaire. Determination of the sample using simple random sampling technique. The process of data analysis using quantitative descriptive analysis. The results showed that the provision of services on population administration based minimum service standards are generally performing well, although still found disparities in its implementation. The imbalance caused by the gap of information about rules and guidelines on minimum service standards between officers and the community.